Perlindungan Hak Waris Perempuan Dalam Perspektif Hukum Adat Bali (Jurnal Begawan Hukum (JBH), 2024)
Customary inheritance law is customary law that regulates the system of inheritance procedures. There are 3 (three) customary inheritance systems in Indonesia, namely the individual inheritance system, the collective inheritance system and the majorate inheritance system. Meanwhile, there are 4 (four) kinds of kinship systems in Indonesia, namely patrilineal, matrilineal, bilateral or parental and alternate kinship systems. Balinese people adhere to the patrilineal kinship system, which is based on descent from the male side. This means that in Balinese society, the male child is Bali, and the position and rights of men are higher than the rights and position of women. In Balinese society, girls have the right to enjoy inheritance as long as they perform their dharma.  The limited right of girls to receive inheritance led to emancipation which demanded that girls get the same inheritance rights as boys. During the Indonesian government, the protection of women's inheritance rights in Bali was further strengthened by various laws and regulations issued by the government. However, there are also factors inhibiting the protection of women's inheritance rights in Bali, namely the strong influence of patriarchal culture in Balinese society and adhering to Balinese customary law which gives greater inheritance rights to men.